Clinical presentation of Spondyloarthropathy: A study of 61 patients - Hasan, Suzon Al; Siddiq, Md Abu Bakar; Hossain, Md Shawkat (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: spondyloarthropathy; clinical presentation doi: 10.3329/jcmcta.v18i2.3823 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):7-10